INTANGIBLE ASSETS, TRANSFER PRICING, DAN PERPAJAKAN SUATU PENDEKATAN STUDI LITERATUR - Ajie Setiawan; Mela Yulia Aprianti; Ratih Jahara Pebriani; Winda Nuraini (Journal of Taxation Analysis and Review, 2021)
This study aims to determine whether the tax imposition rates can influence the company to carry out transfer pricing and to find out how the impact of intangible assets on transfer pricing provisions. Researchers used a sample of 40 journals obtained from google scholar, sinta.ristekbrin.go.id, garuda.ristekbrin.go.id, and www.researchgate.net then presented in several groups using tables including: journal researcher, journal title, year , research methods, research results, dependent variables, and independent variables. The tabulated results of the 40 journals were then classified into a meta-analysis. The results of this study indicate that the more dominant transfer pricing behavior has no effect, this conclusion is obtained from the comparisons made of the results of the study which consisted of journals sampled by the author in this study and the results showed that dominance had no effect.